2023
DOI: 10.3389/fpubh.2022.1090443
|View full text |Cite
|
Sign up to set email alerts
|

Association between air pollution exposure and coronary heart disease hospitalization in a humid sub-tropical region of China: A time-series study

Abstract: ObjectiveEmerging evidence has highlighted the possible links of environmental pollution with several cardiovascular diseases (CVDs). The current study aimed to explore the impact of short-term air pollution exposure on CHD hospitalization in Hefei.MethodsData about the daily number of CHD admissions (from 2014 to 2021) were retrieved from the First Affiliated Hospital of Anhui Medical University. Air pollutants and meteorological data were obtained from the China Environmental Monitoring Station and the China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…In this study, Feng et al [18] examine the correlation between brief exposure to air pollution and the occurrence of hospitalisations due to coronary heart disease (CHD) in Hefei, China. Their examination of daily CHD admissions, in conjunction with air pollution and meteorological data, reveals noteworthy associations between CHD hospitalisation rates and pollutants such as NO2, O3, and CO.…”
Section: Review Of Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, Feng et al [18] examine the correlation between brief exposure to air pollution and the occurrence of hospitalisations due to coronary heart disease (CHD) in Hefei, China. Their examination of daily CHD admissions, in conjunction with air pollution and meteorological data, reveals noteworthy associations between CHD hospitalisation rates and pollutants such as NO2, O3, and CO.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…Some research employs intricate models such as Bi-LSTM, but the modelling approaches differ, leading to incorrect outcomes. Enhancing the reliability and replicability of air pollution studies necessitates the establishment and verification of standardised models [6,18]. Another notable disparity exists in the translation of research findings into impactful legislation and communitylevel initiatives aimed at mitigating the health consequences of air pollution.…”
Section: Understanding and Addressing Challenges In Air Pollution Res...mentioning
confidence: 99%
“…Increasing evidence has shown that major air pollutants, such as PM 2.5 , particulate matter less than 10 μm in aerodynamic diameter (PM 10 ), nitrogen dioxide (NO 2 ) and sulfur dioxide (SO 2 ), carbon monoxide (CO) and ozone (O 3 ), are closely associated with increased risk of morbidity and mortality [ 9 , 10 , 11 , 12 ]. Especially for PM 2.5 , there is growing and consistent evidence that it leads to a sustained increase in mortality from cardiovascular and respiratory diseases [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%